Development of the bond markets in Singapore and Malaysia. - Chan, Wei Lun. (2009)
Developmental strategies for developing the bond markets in Singapore and Malaysia are proposed. The strategies focus on ways to encourage more corporations to issue bonds. The study recommends changes to the existing institutional requirements such as changes to the pre-requisites to obtain approval to issue bonds ; formation of a one-step processing procedure in Malaysia to process applications, and the possibility of forming a rating agency in Singapore. The study also explores avenues for increasing the demand for corporate bonds such as increasing provident fund investments in bonds; changes to the commission rate structure for bond trading, and reduction or abolition of tax for interest received and stamp duty transferances. The study also discusses the impact of existing policies of the internationalisation of the Singapore Dollar and statutory requirements on insurance companies and their impacts on the bond market. As the authorities in Singapore and Malaysia are using different strategies to develop their bond markets, the study discusses ways of strengthening some of the existing vehicles.